Real-Time Mimicking the Electronic Structure of N-Coordinated Ni Single Atoms: NiS-Enabled Electrochemical Reduction of CO2 to CO - Han, Man Ho; Kim, Dongjin; Kim, Sangkuk; Yu, Seung-Ho; Won, Da Hye; Min, Byoung Koun; Chae, Keun Hwa; Lee, Woong Hee; Oh, Hyung-Suk (Wiley-VCH Verlag, 2022)
N-coordinated Ni single atom (Ni-NC) is one of the best catalysts for the CO2 reduction reaction (CO2RR) to produce CO. However, no bulk Ni materials have exhibited high catalytic activity for CO2RR. Herein, it is shown that NiS nanoparticles mimicking the electronic structure of Ni-NC in real-time enhance the CO2RR activity in a zero-gap electrolyzer. In situ/Operando X-ray absorption spectroscopy suggests that under a cathodic potential, the electronic structure of NiS changes similarly to that of Ni-NC and modulated Ox-zSy ligands with similar properties to Ni ligands, resulting in a mimicked electronic structure. However, NiS exhibits low stability owing to the loss of S species, key to mimicking N ligands. The future challenges in finding a stable mimicked electronic structure are discussed. Moreover, this work provides new insights into the development of catalysts from materials that have not generally been considered previously.